Evaluation of efficiency of TVT operation in women with urinary stress incontinence and the frequency of intra- and postoperative complications - Gładysiak, Andrzej; Krzewińska, Hanna; Biesiada, Jan; Szram, Krzysztof; Banach, Renata (Menopause Review/Przegląd Menopauzalny, 2004)
Objectives: Urinary incontinence is one of the most common chronic diseases in women. Various data indicate that from 17% to 60% of population suffer from urinary incontinence. This complaint does not only concern women over 60 years of age but also appears in female patients in their thirties and forties. Design: The aim of our study was to evaluate the efficiency of TVT operation in a group of female patients with urinary stress incontinence and the frequency of intra- and postoperative complications. Materials and methods: Urinary stress incontinence was diagnosed on the basis of patient’s history related to complaints because of the disease, taking into account the description of the situation when involuntary outflow of urine happened. Female patients also underwent a gynecological investigation with a cough test. Urodynamic testing was also executed. The efficiency of treatment of female patients operated using the TVT method was evaluated by estimating urine analysis, bacteriological culture and purity of vagina. Results: We found that five women (10.4%) leak urine at exertion, 2% reported absence of improvement in the postoperative period, however in almost 90% of patients urinary stress incontinence was not found. Conclusions: We found occasional intraoperative complications related to the lesion of urinary bladder’s wall, which did not produce any distant consequences. Postoperative complications, such as urinary tract and vagina infections, suggest the necessity of postoperative assessment of urine analysis and degree of vagina cleanness.